Fracture Healing with Minimal Post Fracture Stiffness through Jingini Taila Bandage: A Case Study - Sreenadh P.; T.S. Dudhamal (Dev Sanskriti: Interdisciplinary International Journal)
Metatarsal fractures are a common type of foot injury that can significantly impact a patient's daily activities. Although such fractures are typically managed through immobilization with a plaster of Paris (POP) cast, the resulting stiffness upon cast removal can delay the patient's return to normal activities due to local tissue stiffness. This study aims to facilitate proper fracture healing while minimizing post-cast stiffness by adhering to traditional Ayurvedic principles of fracture management. This case study presents a 54-year-old female with a closed, oblique, minimally displaced fracture of the fourth metatarsal shaft, managed by integrating Ayurvedic principles and conventional immobilization techniques. Lakshadi Guggulu was given orally and Jingini Taila bandage was applied externally. Complete symptom relief was observed within six weeks, and the patient resumed routine activities without pain or stiffness after just 45 days. The continuous application of Jingini Taila over the fracture site is proposed to pacify aggravated doshas, nourish the Asthi dhatus (bone tissues), promote fracture healing, and minimize post-cast stiffness. This integrative approach potentially reduces the overall healing duration and post-fracture stiffness, facilitating an earlier return to daily activities. Further studies are warranted to establish the broader applicability of combining immobilization with the local application of Jingini Taila in fracture management.